2016
DOI: 10.1016/j.tranon.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative Stress in the Proximal Stomach of Patients with Barrett’s Esophagus and Adenocarcinoma of the Esophagus and Esophagogastric Junction

Abstract: OBJECTIVES: Oxidative stress (OS) is an essential element in the pathogenesis of Barrett’s esophagus (BE) and its transformation to adenocarcinoma (EAC). The state of OS in the proximal stomach of patients with BE and EAC is unknown. Isoprostanes are a specific marker of OS not previously used to determine OS from BE/EAC tissue samples. PATIENTS AND METHODS: OS was measured in 42 patients with BE (n = 9), EAC (n = 9), or both (n = 24) and 15 control patients. A STAT-8-Isoprostane EIA Kit served to identify 8-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Signature 17 is most prominent in gastric cancers and esophageal adenocarcinoma (EAC), where it appears early during disease development [ 42 ], and it is also present in Barrett’s esophagus (BE), a precursor to EAC [ 43 ]. Due to the importance of gastro-esophageal and duodeno-gastric reflux in the development of BE and EAC [ 44 46 ] and the resulting oxidative stress [ 47 50 ], it has been speculated that oxidative damage could cause the mutation patterns characteristic for signature 17 [ 51 , 52 ]. Increased oxidative damage to guanine has been reported in the epithelial cells of dysplastic BE as well as after incubation of BE tissue with a cocktail mimicking bile reflux [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Signature 17 is most prominent in gastric cancers and esophageal adenocarcinoma (EAC), where it appears early during disease development [ 42 ], and it is also present in Barrett’s esophagus (BE), a precursor to EAC [ 43 ]. Due to the importance of gastro-esophageal and duodeno-gastric reflux in the development of BE and EAC [ 44 46 ] and the resulting oxidative stress [ 47 50 ], it has been speculated that oxidative damage could cause the mutation patterns characteristic for signature 17 [ 51 , 52 ]. Increased oxidative damage to guanine has been reported in the epithelial cells of dysplastic BE as well as after incubation of BE tissue with a cocktail mimicking bile reflux [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…We should be careful the elevated levels of 8-oxodG in CAG patients and prevent the potentially occurrence of cancer. Kauppi et al demonstrated that ROS was elevated in the proximal stomach of Barrett’s esophagus and adenocarcinoma patients, which stimulates the proximal stomach mucosa, contributing to the development of cancer in the end [ 27 ]. Ma et al found that the level of 8-oxodG in gastric cancer patients was sharply higher than that in normal [ 28 ].…”
Section: Potential Application In Detection Of Diseasesmentioning
confidence: 99%
“…30 Several studies have revealed the correlation of 8-OHdG with Barrett's esophagus, adenocarcinoma of the esophagus and stomach, gastric atrophy and intestinal metaplasia. 31,32 Therefore, this result is thought to be a demonstration of the antioxidative and gastric protective effect of GCWB104, because 8-OHdG has been significantly decreased in the test group, although it is difficult to interpret that it contributes directly to improving GI function.…”
Section: Discussionmentioning
confidence: 89%